THE ARRANGEMENT CONCEPTS FOR ENVIRONMENTALLY SUSTAINABLE HOUSING LAND - Desy Rahmadaniyati; Rika Kisnarini; Dewi Septanti (Journal of Architecture&ENVIRONMENT, 2016)
The issue of global urbanization gives rise to variety of urban phenomena, including the urban land scarcity and the high demand for decent dwellings. On one hand, in response to the land scarcity, the urban housing developments should be directed to a sustainable process that can take place between generations. On the other hand, housing developments also have direct impacts on the environment quality degradation. Thus, further learnings about more efficient use for housing land are needed, one of which can be learned from the already built formal housing designs in Indonesia. Therefore, this study aims to propose concepts for formal housing land arrangement to ensure the environmental sustainability. The case study of this research is Taman Wisata Regency located on the border of the city of Surabaya and Gresik, Indonesia. The data of field’s existing conditions, potentials, and problems, were collected through observation and documentation. The data were analyzed descriptive and qualitative based on the criteria of sustainable housing from UN-Habitat. The results show that the land efficiency on Taman Wisata Regency can be done in the form of rearrangement proposal of prone area anticipation, the opening of inbound access from one-gate to two-gates system, the arrangement of road’s circulation and proportion, the maximization of green open spaces, and also quality improvement of other infrastructures such as drainage and waste management. The results of this study are expected to be used as reference for planners, designers or developers, in creating the environmentally sustainable housing land.